L-type calcium channel blockers, morphine and pain: Newer insights - Kumar, Rakesh (Medknow Publications, 2010)
Earlier, we had reported that co-administration of opioids and L-type calcium channel blockers (L-CCBs) like diltiazem could prove useful in the treatment of cancer pain. Much of this report was based upon earlier published work involving animal models of pain exposed to brief periods of noxious radiant heat without any tissue injury. However, pain in clinical situations usually result from tissue injury. Thus, the aim of the current investigation was to study the analgesic effect of this combination of drugs in the rat formalin test which is associated with actual tissue injury. Wistar rats (n=60) received either L-CCB (nifedipine/nimodipine/verapamil/diltiazem i.p.) or morphine (s.c.) or both drugs. The formalin test was done 30 min after morphine or placebo injection. The naloxone reversal test was also done. Administration of L-CCBs alone, particularly diltiazem, increased pain in the formalin test. In contrast, co-administration of these L-CCBs with morphine led to decreased pain response, though statistically significant decrease was noted only with nimodipine + morphine. Naloxone reversed this analgesic effect, indicating that it was primarily an opioid-mediated effect. The results show that administration of L-CCBs alone may prove counterproductive in the therapeutic management of pain (anti-analgesic effect). However, co-administration of both drugs (morphine and nimodipine) in quick succession could lead to adequate pain relief.